The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12879-019-4750-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of a rapid recombinase-aided amplification assay for Mycoplasma pneumoniae detection

Abstract: Background: Mycoplasma pneumoniae is one of the most common causative pathogens of community-acquired pneumonia (CAP), accounting for as many as 30-50% of CAP during peak years. An early and rapid diagnostic method is key for guiding clinicians in their choice of antibiotics. Methods: The recombinase-aided amplification (RAA) assay is a recently developed, rapid detection method that has been used for the detection of several pathogens. The assays were performed in a one-step single tube reaction at 39°Celsius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…RAA is a new technology developed by China that accords with rapid detection demands in our country (36). It has significant advantages, and has been widely used in detecting pathogens (37)(38)(39)(40)(41). In this study, we developed the PCV2 RAA-strip which is simple, sensitive, specific for rapid detection of PCV2 within 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…RAA is a new technology developed by China that accords with rapid detection demands in our country (36). It has significant advantages, and has been widely used in detecting pathogens (37)(38)(39)(40)(41). In this study, we developed the PCV2 RAA-strip which is simple, sensitive, specific for rapid detection of PCV2 within 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…MP strains harbor multiple genotypes ( Xiao et al, 2015 ; Meyer Sauteur et al, 2021b ), and genetic variants within the target region may lead to false negative results for molecular diagnosis ( Unckless et al, 2017 ; Merida-Vieyra et al, 2019 ; Xue et al, 2020 ). In previous studies, P1 , CARDS toxin , ATPase , 16S rRNA , 23S rRNA , RepMp1 and RepMP4 have been reported as target sequence ( Dumke et al, 2007 ; Winchell et al, 2008 ; Zhou et al, 2015 ; Leal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, P1 , CARDS toxin , ATPase , 16S rRNA , 23S rRNA , RepMp1 and RepMP4 have been reported as target sequence ( Dumke et al, 2007 ; Winchell et al, 2008 ; Zhou et al, 2015 ; Leal et al, 2020 ). Among them, P1 gene has been demonstrated to be high selective and efficient for sequence detection ( Merida-Vieyra et al, 2019 ; Xue et al, 2020 ). P1 gene encodes an important 170-kDa protein as the major adhesion protein, which is essential for MP infection and successful colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinase-aided amplification (RAA), a kind of isothermal nucleic acid amplification method, can be performed at constant temperatures (37-42°C; Qin et al, 2021) and has a short detection time (less than 20 min) and high sensitivity (Shen et al, 2019). Recombinase-aided amplification does not require a complex instrument to provide cyclic temperature (Xue et al, 2020), which makes it more convenient in resource-poor settings than PCR. In this study, the specific fluorescence probe was added in the RAA system to achieve real-time fluorescence analysis.…”
Section: Introductionmentioning
confidence: 99%